Electric Bed Design and Features for Next Generation of Bedside Nursing - Zoabli, Gnahoua (CMBES Proceedings, 2017)
On Easter Sunday 2016, I was hospitalized for a week at the brief hospitalization unit of St- Eustache Hospital; An institution of which I am the chief of biomedical engineering since September 9, 2009. Beyond the great technological achievements that I benefited as a patient, I noticed a few dysfunctions from the point of view of the patient that I became. The purpose of this article is to suggest a better arrangement of medical devices at the bedside of the patient to improve his episode of care. Based on the premise that any medical device basically at the patient's bedside should be incorporated into the bed, if technologically possible, we propose the design of a first-generation intelligent medical bed, using current bedside concepts, embedded or not. Some improvements are also proposed for the accessibility of the patient to the controls of existing beds. The second generation will focus on patient communication with the nursing station. Thus, the patient call will be graded and interpreted to discriminate the regular calls to medical emergencies. The third generation will consider network communication and the incorporation of medical and pharmacological transactions from the bedside to the patient record via the bed that will be networked and the patient, geographically identifiable, in real time. One of the objectives of this article is to encourage healthcare professionals who would eventually become a client of the healthcare network to report their observations and thus contribute to alter the services from within.